Early Pregnancy Failure: Medical versus Surgical Management - Begum, Nasima; Akhter, Shahnaz; Laila, Luna (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Misoprostol is increasingly used to treat women who have a failed pregnancy may be due to blighted ovum (anembryonic gestation), incomplete abortion, missed abortion, inevitable abortion in the first trimester. Medical treatment with Misoprostol is an alternative to conventional surgical treatment. Use of Misoprostol is simple, highly acceptable, noninvasive and preferred by women. In addition to surgical risk and patient's preference, medical evacuation reduces the need for hospital stay and the overall management cost. Objective: To determine the efficacy and safety of Misoprostol for evacuation of uterus in early pregnancy loss and to compare the result with surgical evacuation. Materials and Methods: It was a prospective randomized study conducted on 50 patients at the department of Obstetrics and Gynaecology, Border Guard Hospital, Dhaka during the period from February 2018 to July 2019. Here 25 patients received Misoprostol as medical treatment and 25 patients received surgical treatment. Results: Of the 25 women assigned to receive Misoprostol, 19(76%) had complete expulsion by 24 hours and 22(88%) by 7 days. Complete evacuation after 1st dose was 68% and after 2nd dose 88%. Misoprostol treatment failed in 3(12%) cases and required surgical evacuation. Among the respondents 80% women stated that they would use Misoprostol again if the need arises. Conclusion: Medical treatment with Misoprostol is a cheaper alternative to surgery. Given its success rate near about 88% with mild side effects controllable with additional medication and above all patient’s satisfaction, it should be prioritized over the evacuation curettage in patients who meet the treatment criteria. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 63-67